If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16x-3=10x+18
We move all terms to the left:
16x-3-(10x+18)=0
We get rid of parentheses
16x-10x-18-3=0
We add all the numbers together, and all the variables
6x-21=0
We move all terms containing x to the left, all other terms to the right
6x=21
x=21/6
x=3+1/2
| x(x+5)=73 | | 3.4+x=18 | | 9-1/3=5/3n | | N^=5n | | 10x–15=85 | | 3(3x−1)=9x+7 | | (2x-8)=(3x-12) | | H(4)=-16(4)^2+68t+2 | | 2/3m-5=13 | | 3.8x-8.5=10.5 | | 9u+8u=2^0 | | 2.5(2z+5)=5(5(z+2.5) | | 0.1x+0.001=1/100(x+10 | | |1/2y+8|=|1/5y+2| | | 3(8x+2)=6x-10 | | |-12|-n=19 | | 18=1/2(r^2)(1/9) | | 2m+7m=10 | | (3/7)w-11=(-4/7w) | | 1/3m-6=5 | | 2*y+13=75 | | 4-7+4c=7c+6 | | 2xY+13=75 | | -3(x-2)+x=24 | | 10-5t+10=40 | | 012=x0.6 | | 19=t-7+4t | | 10r+7=18 | | 4/3(5b+3)=-2b | | 12 =8k | | 73=13^x | | -1-7/x=-6x |